Case report: HLA-haploidentical HSCT rescued with donor lymphocytes infusions in a patient with X-linked chronic granulomatous disease - Scheiermann, Julia; Künkele, Annette; von Stackelberg, Arend; Eggert, Angelika; Lang, Peter; Zirngibl, Felix; Martin, Luise; Schulte, Johannes Hubertus; von Bernuth, Horst (Frontiers in Immunology, 2023)
Chronic granulomatous disease is an inborn error of immunity due to disrupted function of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. This results in impaired respiratory burst of phagocytes and insufficient killing of bacteria and fungi. Patients with chronic granulomatous disease are at increased risk for infections, autoinflammation and autoimmunity. Allogeneic hematopoietic stem cell transplantation (HSCT) is the only widely available curative therapy. While HSCT from human leukocyte antigen (HLA) matched siblings or unrelated donors are standard of care, transplantation from HLA-haploidentical donors or gene therapy are considered alternative options. We describe a 14-month-old male with X-linked chronic granulomatous disease who underwent a paternal HLA-haploidentical HSCT using T-cell receptor (TCR) alpha/beta+/CD19+ depleted peripheral blood stem cells followed by mycophenolate graft versus host disease prophylaxis. Decreasing donor fraction of CD3+ T cells was overcome by repeated infusions of donor lymphocytes from the paternal HLA-haploidentical donor. The patient achieved normalized respiratory burst and full donor chimerism. He remained disease-free off any antibiotic prophylaxis for more than three years after HLA-haploidentical HSCT. In patients with x-linked chronic granulomatous disease without a matched donor paternal HLA-haploidentical HSCT is a treatment option worth to consider. Administration of donor lymphocytes can prevent imminent graft failure.